Marriage: A Conflict between Dreams and Demands in William Dean Howells’ Their Wedding Journey - SP. , Shanthi (International Journal of Psychosocial Rehabilitation, 2020)
Their Wedding Journey is an unpretentious presentation at the beginning of Howells career to exploit those traits of skillful justification and elegance of style that had previously won recognition for his earlier narratives. The form of the description is rather strange – “-story, half-travel sketch,” as Howells once called it—and it is not surprising that readers have tended to ignore the story while flattering the sketch.